Community-Based and System-Level Interventions for Improving Food Security and Nutritious Food Consumption: A Systematic Review. Issue 2 (4th March 2022) - Ezekekwu, Emmanuel; Salunkhe, Sonali S.; Jennings, J'Aime C.; Kelly Pryor, Brandy N.
ABSTRACT: As studies examining the effectiveness of food security interventions collectively are sparse, this review examined the most effective community-based and system-level interventions that have increased nutritious food consumption across food-insecure populations. Following PRISMA-guidelines, 22 articles included were classified into six categories: Educational and Behavioral Programs; Fresh Fruit and Vegetable Programs; Summer Electronic Benefits Transfer; Discounted Food Options; Emergency Food Assistance Programs; and Multicomponent Programs. This review concludes that future considerations for positively impacting food security and nutritious food intake should give attention to community and system-level multicomponent interventions that address the specific social and economic barriers facing the target population.